2017
DOI: 10.12688/wellcomeopenres.12338.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of inherited red blood cell disorders in pregnant women of different ethnicities living along the Thailand-Myanmar border

Abstract: Background: Inherited red blood cell disorders are prevalent in populations living in malaria endemic areas; G6PD deficiency is associated with oxidant-induced haemolysis and abnormal haemoglobin variants may cause chronic anaemia. In pregnant women, microcytic anaemia caused by haemoglobinopathies mimics iron deficiency, complicating diagnosis and treatment. Anaemia during pregnancy is associated with morbidity and mortality. The aim of this study was to characterise the prevalence of G6PD deficiency and haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…The highest prevalence of G6PD deficiency is found in malaria endemic regions 1 , 15 . In the population attending Shoklo Malaria Research Unit (SMRU) clinics, the prevalence of G6PD deficiency is 13.7% in adult males 16 and 2–4% in adult females 17 and neonatal hyperbilirubinemia is common 18 . Routine neonatal screening for G6PD deficiency is therefore recommended in this setting 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The highest prevalence of G6PD deficiency is found in malaria endemic regions 1 , 15 . In the population attending Shoklo Malaria Research Unit (SMRU) clinics, the prevalence of G6PD deficiency is 13.7% in adult males 16 and 2–4% in adult females 17 and neonatal hyperbilirubinemia is common 18 . Routine neonatal screening for G6PD deficiency is therefore recommended in this setting 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that a fluorescent spot test (or an equivalent RDT) would classify heterozygous females with a G6PD activity as low as 30-40% as G6PD normal. In fact, Bancone et al found that 60% of G6PD heterozygous females were misdiagnosed by qualitative screening [28]. Due to the loss of G6PD-deficient cells to haemolysis during illness, heterozygote females with even less than 30-40% activity could be misdiagnosed as normal if the test is done Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the previous quantification of the G6PD activity during the haemolytic episode was considered unreliable (due to increased reticulocyte count and low Hb level), the staff offered the woman to repeat quantitative G6PD testing while in steady state (HCT 36.1%). This time the G6PD activity was found to be 4.62 IU/gHb, which corresponds to 62% of the population mean and is highly suggestive of G6PD heterozygosity [28]. Following this new finding, the patient and infant were screened for the most common G6PD gene mutations seen in the area (Mahidol, Chinese-4, Viangchan, Mediterranean variants) [29].…”
Section: Additional Laboratory Findings Following Radical Curementioning
confidence: 97%
“…In this study, parasite density by assumed RBC count of 5.0 x10 6 /µL (for males) and 4.5 x10 6 /µL (for females) showed overestimation, possibly people living in Thailand including Thai and other ethnicities from Myanmar had underlying anemia due to hemoglobinopathy (which is commonly found) [13,14] and intestinal parasitic infection [15][16][17][18][19] causing lower exactly assumed RBC counts in these population in Thailand.…”
Section: Discussionmentioning
confidence: 99%